Growth Failure and Excessive Weight Gain in a 10 Year Old Male With Obesity: Approach to Diagnosis, Management, and Treatment of Acquired Hypothyroidism - Schumaker, Tiffany; Censani, Marisa (Frontiers in Pediatrics, 2018)
We report the case of a 10 year old male with severe obesity who presented with a 2 year history of significant growth failure and excessive weight gain that was subsequently diagnosed with serum negative Hashimoto's thyroiditis and acquired hypothyroidism. Initial investigations revealed a markedly elevated thyroid stimulating hormone concentration >100uIU/mL and an undetectable free thyroxine with total thyroxine 0.56 ug/dL. Thyroid antibodies were negative, however ultrasound findings were consistent with Hashimoto's thyroiditis. After treatment with levothyroxine supplementation, he had significant weight loss and marked improvement in his growth velocity. This case emphasizes the need to recognize excessive weight gain and growth failure as an initial presentation of Hashimoto’s thyroiditis and highlights management and approach to treatment. Diagnosis and treatment is vital as prolonged undiagnosed hypothyroidism can result in incomplete catch up growth and compromised final adult height.